Interactions Between Environmental Factors and Zinc Concentrations in Porewater and Roots of Rhizophora sp. in Ampallas, Mamuju, West Sulawesi, Indonesia - Rantih Isyrini; Shinta Werorilangi; Supriadi Mashoreng; Ahmad Faizal; Rastina Rachim; Akbar Tahir (Universitas Jenderal Soedirman, 2018)
The study was to determine the concentrations of Zn in porewater and fine roots of Rhizophora sp., and to examine their interactions with mangrove densities and physico-chemical. Porewater samples, fine roots, and sediments were collected in a 100 m2 plot at each site with different mangrove densities. The average Zn concentrations in mangrove roots in the study area were 0 – 58.21 mg/kg, suggested the capability of mangrove roots in retaining Zn. The average dissolved Zn concentrations in porewater were 0.63 mg/L – 3.50 mg/L, illustrated the amount of Zn bioavailable form and its potential release to the adjacent environment. The Zn concentrations in porewater did not correlate significantly with the densities of mangroves. The concentrations of Zn in roots increased as the densities were higher, which is possibly caused by the absence of mangrove at Site 1. The study discovered the important roles of organic content and silt/clay in Zn sorption thus affect Zn levels in porewater. The concentrations of Zn in mangrove roots increased as the pH of sediment and porewater decreased.